Challenges in Interpretation of Thyroid Function Tests in Pregnant Women with Autoimmune Thyroid Disease. (10th February 2011) - Feldt-Rasmussen, Ulla; Bliddal Mortensen, Anne-Sofie; Rasmussen, Åse Krogh; Boas, Malene; Hilsted, Linda; Main, Katharina
Abstract : Physiological changes during gestation are important to be aware of in measurement and interpretation of thyroid function tests in women with autoimmune thyroid diseases. Thyroid autoimmune activity is decreasing in pregnancy. Measurement of serum TSH is the first-line screening variable for thyroid dysfunction also in pregnancy. However, using serum TSH for control of treatment of maternal thyroid autoimmunity infers a risk for compromised foetal development. Peripheral thyroid hormone values are highly different among laboratories, and there is a need for laboratory-specific gestational age-related reference ranges. Equally important, the intraindividual variability of the thyroid hormone measurements is much narrower than the interindividual variation (reflecting the reference interval). The best laboratory assessment of thyroid function is a free thyroid hormone estimate combined with TSH. Measurement of antithyroperoxidase and/or TSH receptor antibodies adds to the differential diagnosis of autoimmune and nonautoimmune thyroid diseases.